In-depth proteomic characterization of Schistosoma haematobium: Towards the development of new tools for elimination. - Javier Sotillo; Mark S Pearson; Luke Becker; Gebeyaw G Mekonnen; Abena S Amoah; Govert van Dam; Paul L A M Corstjens; Janice Murray; Takafira Mduluza; Francisca Mutapi; Alex Loukas (Public Library of Science (PLoS), 2019)
Background Schistosomiasis is a neglected disease affecting hundreds of millions worldwide. Of the three main species affecting humans, Schistosoma haematobium is the most common, and is the leading cause of urogenital schistosomiasis. S. haematobium infection can cause different urogenital clinical complications, particularly in the bladder, and furthermore, this parasite has been strongly linked with squamous cell carcinoma. A comprehensive analysis of the molecular composition of its different proteomes will contribute to developing new tools against this devastating disease. Methods and findings By combining a comprehensive protein fractionation approach consisting of OFFGEL electrophoresis with high-throughput mass spectrometry, we have performed the first in-depth characterisation of the different discrete proteomes of S. haematobium that are predicted to interact with human host tissues, including the secreted and tegumental proteomes of adult flukes and secreted and soluble egg proteomes. A total of 662, 239, 210 and 138 proteins were found in the adult tegument, adult secreted, soluble egg and secreted egg proteomes, respectively. In addition, we probed these distinct proteomes with urine to assess urinary antibody responses from naturally infected human subjects with different infection intensities, and identified adult fluke secreted and tegument extracts as being the best predictors of infection. Conclusion We provide a comprehensive dataset of proteins from the adult and egg stages of S. haematobium and highlight their utility as diagnostic markers of infection intensity. Protein composition was markedly different between the different extracts, highlighting the distinct subsets of proteins that different development stages present in their different niches. Furthermore, we have identified adult fluke ES and tegument extracts as best predictors of infection using urine antibodies of naturally infected people. This study provides the first steps towards the development of novel tools to control this important neglected tropical disease.